The Rodent Models of Dyskinesia and Their Behavioral Assessment - Peng, Qiwei; Zhong, Shaoping; Tan, Yang; Zeng, WeiQi; Wang, Ji; Cheng, Chi; Yang, Xiaoman; Wu, Yi; Cao, Xuebing; Xu, Yan (Frontiers in Neurology, 2019)
Dyskinesia, a major motor complication resulting from dopamine replacement treatment, manifests as involuntary hyperkinetic or dystonic movements. This condition poses a challenge to the treatment of Parkinson's disease. So far, several behavioral models based on rodent with dyskinesia have been established. These models have provided an important platform for evaluating the curative effect of drugs at the preclinical research level over the past two decades. However, there are differences in the modeling and behavioral testing procedures among various laboratories which adversely affect the rat and mouse models as credible experimental tools in this field. This article systematically reviews the history, the pros and cons, and the controversies surrounding rodent models of dyskinesia as well as their behavioral assessment protocols. A summary of factors that influence the behavioral assessment in the rodent dyskinesia models is also presented, including the degree of dopamine denervation, stereotaxic lesion sites, drug regimen, monitoring styles, priming effect, and individual and strain differences. Besides, recent breakthroughs like the genetic mouse models and the bilateral intoxication models for dyskinesia are also discussed.